Universal CRISPR/Cas12a-associated aptasensor suitable for rapid detection of small proteins with a plate reader - Li, Yi; Liu, Linyang; Qiao, Laicong; Deng, Fei (Frontiers in Bioengineering and Biotechnology, 2023)
With the discovery of its collateral cleavage activity, CRISPR/Cas12a has recently been identified as a key enabling approach in novel DNA biosensor development. Despite its remarkable success in nucleic acid detection, realizing a universal CRISPR/Cas biosensing system for non-nucleic acid targets remains challenging, particularly at the extreme high sensitivity ranges for analyte concentrations lower than pM-level. DNA aptamers can be designed to bind to a range of specific target molecules, such as proteins, small molecules, cells, etc., with high affinity and specificity through configuration changes. Here, by harnessing its diverse analyte binding ability and also redirecting the specific DNA cutting activity of Cas12a to selected aptamers, a simple, sensitive and universal biosensing platform has been established, termed CRISPR/Cas and Aptamer Mediated Extra-sensitive Assay (CAMERA). With simple modifications to the aptamer and guiding RNA of Cas12a RNP, CAMERA demonstrated 100 fM sensitivity for targeting small proteins such as IFN-γ and insulin with less than 1.5-hour detection time. Comparing with the gold-standard ELISA, CAMERA achieved higher sensitivity and shorter detection time, while retaining ELISA’s simple setup. By replacing the antibody with aptamer, CAMERA also achieved improved thermal stability allowing to eliminate the requirement for cold storage. CAMERA has the potential to be used as one replacement of conventional ELISA for a variety of diagnostics, but with no significant changes for experimental setup.